ASSOCIATION BETWEEN SIC AND DIC SCORES IN SEPTIC SHOCK PATIENTS (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the relationship between the SIC score and DIC score in patients with septic shock at University Medical Center Ho Chi Minh City.Methods: A prospective follow-up study was conducted on 47 newly diagnosed septic shock patients admitted to the Intensive Care Unit between June 2023 and June 2024.Results: The mean age was 69.77 ± 14.54 years, with a male-to-female ratio of 0.8/1. Patients aged ≥ 60 years had a significantly higher prevalence of comorbidities compared to younger patients. The prevalence of patients with SIC was 65.96%, and with DIC was 29.79%. Overt DIC occurred only in patients who met the SIC criteria, with a statistically significant association (p = 0.001). Thrombocytopenia, decreased fibrinogen, elevated D-dimer, and fibrin monomer were strongly associated with overt DIC, whereas INR had limited value.Conclusion: The SIC score enables early recognition of sepsis-induced coagulopathy and predicts progression to overt DIC, supporting timely risk stratification and clinical management.
Keywords: Septic shock, septic induced coagulopathy, disseminated intravascular coagulation.